Law and orders: the orders of the European Court of Justice as a window in the judicial process and institutional transformations. Issue 3 (September 2022) - Šadl, Urška; López Zurita, Lucía; Arne Brekke, Stein; Naurin, Daniel
Abstract: Orders are judicial decisions designed to shore up fair and timely resolution of disputes. As written, detailed, and factual documents, they are reliable markers of procedural steps and a unique source of information about the inner working of an institution. This article examines all published orders of the European Court of Justice, drawing lessons from their use. The analysis demonstrates that the pursuit of efficiency and uniform application blurs the lines between the administration and judging. First, it centralises the institution, expanding the duties of the Registry and amplifying the role of the Cabinet of the President of the Court. Second, it bureaucratises the interpretation and the uniform application of European Union law. These processes are common in judicial institutions with no power over their dockets. But the particular European response, authored by the Court, also suggests its reluctance to forfeit the interpretive monopoly.